0.16(36-24x)=0.66(9-6x)

Simple and best practice solution for 0.16(36-24x)=0.66(9-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.16(36-24x)=0.66(9-6x) equation:


Simplifying
0.16(36 + -24x) = 0.66(9 + -6x)
(36 * 0.16 + -24x * 0.16) = 0.66(9 + -6x)
(5.76 + -3.84x) = 0.66(9 + -6x)
5.76 + -3.84x = (9 * 0.66 + -6x * 0.66)
5.76 + -3.84x = (5.94 + -3.96x)

Solving
5.76 + -3.84x = 5.94 + -3.96x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3.96x' to each side of the equation.
5.76 + -3.84x + 3.96x = 5.94 + -3.96x + 3.96x

Combine like terms: -3.84x + 3.96x = 0.12x
5.76 + 0.12x = 5.94 + -3.96x + 3.96x

Combine like terms: -3.96x + 3.96x = 0.00
5.76 + 0.12x = 5.94 + 0.00
5.76 + 0.12x = 5.94

Add '-5.76' to each side of the equation.
5.76 + -5.76 + 0.12x = 5.94 + -5.76

Combine like terms: 5.76 + -5.76 = 0.00
0.00 + 0.12x = 5.94 + -5.76
0.12x = 5.94 + -5.76

Combine like terms: 5.94 + -5.76 = 0.18
0.12x = 0.18

Divide each side by '0.12'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 7b-2+3b=30+6b | | 4x=4096 | | -13-3z=12-4y | | y+14=3y+2 | | x-7*x*450=0 | | 0.16(36-24x)=0.66 | | 2x=1024 | | 2.5+8= | | z*3=2*(z+1) | | 7(9n+9)=315 | | 2x+4.5=21 | | 18x^2+216=0 | | ax+bk=t | | z*3=2*z+1 | | 7x^2-12x^2+5=0 | | 20-5m=45 | | -6a-(4b-12a+7c)= | | 2(2+3x)+2(2x-1)=3(x+6) | | 729=0 | | 7x+37=149 | | 5c+4=(-26) | | 9t+17=-1 | | 8t-9+4t=59-5t | | x+7=31 | | (x+14)+(3x-18)=180 | | (9x+2)+(2x)=90 | | 7(7-1*1)=42 | | 9(7t+6)=306 | | 15-10t+7+8t= | | -4(x+3)(x+3)+5=-8 | | 7x-7x-1=42 | | 68-5= |

Equations solver categories